Video Transmission over MIMO-OFDM System: MDC and Space-Time Coding-Based Approaches. (13th March 2007) - Zheng, Haifeng; Ru, Congchong; Chen, Chang Wen; Yu, Lun
Abstract : MIMO-OFDM is a promising technique for the broadband wireless communication system. In this paper, we propose a novel scheme that integrates multiple-description coding (MDC), error-resilient video coding, and unequal error protection strategy with hybrid space-time coding structure for robust video transmission over MIMO-OFDM system. The proposed MDC coder generates multiple bitstreams of equal importance which are very suitable for multiple-antennas system. Furthermore, according to the contribution to the reconstructed video quality, we apply unequal error protection strategy using BLAST and STBC space-time codes for each video bitstream. Experimental results have demonstrated that the proposed scheme can be an excellent alternative to achieve desired tradeoff between the reconstructed video quality and the transmission efficiency.